Discovery and development of natural heat shock protein 90 inhibitors in cancer treatment - Yong Li; Dongmei Zhang; Jun Xu; Junmin Shi; Lei Jiang; Nan Yao; Wencai Ye (Elsevier, 2012)
Heat shock protein 90 (Hsp90) is a highly conserved molecular chaperone that plays a vital role in the signal transduction of cancers. Hsp90 inhibitors are able to inhibit Hsp90 or the complex of Hsp90 and co-chaperones resulting in the degradation of Hsp90-dependent client proteins through the ubiquitination-proteasome pathway, thereby leading to the growth inhibition of tumor cells. This review will briefly discuss the molecular structure and biological function of Hsp90, and focus on a summary of recent progress in the development and testing of natural Hsp90 inhibitors and their different means by which they interact with Hsp90.